2019
DOI: 10.1038/s41431-019-0351-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of couple-based expanded carrier screening offered by general practitioners

Abstract: Expanded carrier screening (ECS) aims to inform couples’ reproductive choice, preferably before conception. As part of an implementation study in which trained general practitioners (GPs) offered a population-based ECS couple-test, we evaluated the feasibility of the test-offer and degree of participant informed choice (IC). Trained GPs from nine practices in the northern Netherlands invited 4295 female patients aged 18–40 to take part in couple-based ECS. Inclusion criteria were having a male partner, plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 23 publications
1
87
0
Order By: Relevance
“…Further work would be required using samples from both affected patients (with as wide a range of variant types as is relevant to the disorder to be screened for) and a cohort representative of the population to be screened. Although the aim of this study was to assess the potential of targeted NGS in routine NBS, targeted NGS from DBS may also be applicable in a range of other clinical pathways [8991]. This assay thus provides a basis for further work to develop cost effective, fast, high throughput targeted NGS from DBS.…”
Section: Discussionmentioning
confidence: 99%
“…Further work would be required using samples from both affected patients (with as wide a range of variant types as is relevant to the disorder to be screened for) and a cohort representative of the population to be screened. Although the aim of this study was to assess the potential of targeted NGS in routine NBS, targeted NGS from DBS may also be applicable in a range of other clinical pathways [8991]. This assay thus provides a basis for further work to develop cost effective, fast, high throughput targeted NGS from DBS.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the gene panel also imposes potential technical constraints, in terms of the requirement to analyze and report large numbers of variants. For this study, the use of a couples-based approach to analysis, with autosomal variants reported only if both partners carry a variant that meets reporting criteria, means that the burden of analysis is markedly reduced compared with reporting individual variant information, removing this as a constraint on panel design [14,15]. A couples-based approach also greatly reduces the genetic counseling requirements for the study [16].…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Mackenzie's Mission is one of several large scale population-based RCS initiatives globally that have curated large panels of genes to test using a couplebased model. 5, 10,13 It is important for participants to understand that RCS is designed to provide the couple with information that might help with decisions about reproduction, rather than to convey genetic risk information for their own health. Participants will also be encouraged and supported to reflect on their values and their goals for testing, to help them decide whether this screening will be useful or important for them.…”
Section: Consent For Rcs: Enabling Meaningful Choicesmentioning
confidence: 99%